Significance of eosinophils in diagnosis of microfilaria among rural population of north India - Dayal, Seema (Journal of Chitwan Medical College, 2017)
Micro filarial infection is a common infection in India. In most of the cases microfilaria is an incidental finding in FNA smears prepared from swellings from various locations in the body Eosinophilia is generally associated with filarial infection. This study was conducted to know the association of microfilaria infection with different age group , clinical characters, eosinophilia. Method and Material: This study was done in Department of Pathology in Rural institute of Medical Sciences & Research Saifai Etawah (U.P.), India. Here, we include 30 cases which was clinically suspicious for microfilaria and also involves others in which microfilaria was incidental finding. Usually peripheral blood examination, FNAC and biopsy are done for the diagnosis of microfilaria. Result: The age of patients was from 16 years to 80 years. Maximum number of patients was of 21-30 years (33.33%). Swelling was chief clinical complaint (66.66%). Raised leucocyte count (70%), eosinophilia (33.33%) on blood smears, eosinophilia on cytology smears (26.66%) and raised erythrocyte sedimentation rate (46.66 %) were seen. Conclusion: Microfilaria infection is common health problem. Careful screening for microfilaria should be done in symptomatic and asymptomatic patients. Eosinophila is though usually seen with microfilaria infection but it is not mandatory to always found eosinophilia with microfilaria infection.